2019
DOI: 10.1073/pnas.1821442116
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mutations at the EGFR ectodomain structurally converge to remove a steric hindrance on a kinase-coupled cryptic epitope

Abstract: Epidermal growth factor receptor (EGFR) signaling is initiated by a large ligand-favored conformational change of the extracellular domain (ECD) from a closed, self-inhibited tethered monomer, to an open untethered state, which exposes a loop required for strong dimerization and activation. In glioblastomas (GBMs), structurally heterogeneous missense and deletion mutations concentrate at the ECD for unclear reasons. We explore the conformational impact of GBM missense mutations, combining elastic network model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 45 publications
5
55
0
1
Order By: Relevance
“…In EGFR-Viii Tyr270 of the YDK triad is lost, while for EGFR-Vii both Asp587 and Lys609 are lost, thereby preventing adoption of the inactive tethered position and promoting formation of an extended conformation that is poised for dimerization. Indeed, this mechanism has been described for several EGFR mutations expressed in GBM (21). Previous studies have also shown that the oncogenic activation of EGFR-Viii may be attributed to disulfide bond-mediated covalent dimerization of the extracellular domain (22,23).…”
Section: The Oncogenicity Of Allosteric Egfr Oncogenes In Gbm Is Medimentioning
confidence: 77%
See 1 more Smart Citation
“…In EGFR-Viii Tyr270 of the YDK triad is lost, while for EGFR-Vii both Asp587 and Lys609 are lost, thereby preventing adoption of the inactive tethered position and promoting formation of an extended conformation that is poised for dimerization. Indeed, this mechanism has been described for several EGFR mutations expressed in GBM (21). Previous studies have also shown that the oncogenic activation of EGFR-Viii may be attributed to disulfide bond-mediated covalent dimerization of the extracellular domain (22,23).…”
Section: The Oncogenicity Of Allosteric Egfr Oncogenes In Gbm Is Medimentioning
confidence: 77%
“…Other studies have attributed the oncogenic activation of EGFR-Viii to the disruption of auto-inhibitory tethering of the extracellular domain, as key interactions at the CR1-CR2 contact point that control the inactive tethered conformation will be lost as a result of this truncation (21). Indeed, auto-inhibitory tethering is also likely disrupted for the EGFR-Vvi oncogene as the tethering contact point at the CR2 site is lost.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, conclusions from studies on EGFR-TKIs/immunotherapies can only be drawn concerning this particular tumor. Finally, as Orellana et al recently suggested the high probability that mutated ectodomain of EGFR vIII induces structural changes in the intracellular kinase domain [183], further research focused on detailed understanding of molecular aspects of EGFR vIII should be expected. On the other hand, considering current standard therapeutic GB regimen, EGFR vIII is associated with prolonged survival of GB patients treated with surgery and radio/chemotherapy [192].…”
Section: Journal Of Oncologymentioning
confidence: 99%
“…erefore, the verification whether glioblastoma patients with high frequency of EGFR mutations respond to TKIs is completely justified, even despite different EGFR mutational spectrum. is becomes even more important since Orellana et al showed that ectodomain EGFR mutations including those leading to EGFR vIII may sensitize tumor cells to tyrosine kinase inhibitors [183]. Reports from in vitro studies conducted on EGFR vIII -expressing cell lines tend to be contradictory.…”
Section: Journal Of Oncologymentioning
confidence: 99%
“…Their contribution to HNSCC pathogenesis and therapy response has received little attention but could have therapeutic implications [7]. It has been demonstrated that EGFR ECD missense mutations can unexpectedly cause spontaneous receptor untethering that removes a restraint on RTK activation and that such mutants can be targeted by specific monoclonal antibodies (mAbs) [11].…”
Section: Introductionmentioning
confidence: 99%